Quality Management in Tanzania - Mohamed, Samira Said Salim (2006)
Increased globalisation and awareness have forced the subject of Quality Management (QM) into the spotlight. More and more, people have awakened to the importance of quality and now regard it as crucial in influencing their retail, or otherwise, decisions. Businesses employing the latest quality techniques realise significant advantages over those that do not. The trend towards quality has not just swept across developed countries but also, increasingly, towards developing countries. Many studies have been conducted regarding the subject, and findings have shown that quality techniques can be successfully adopted by less developed countries. In fact, studies suggest some quality techniques like TQM could actually be more appropriate, in terms of their alignment in some cultural dimensions, to countries in Africa than to other more developed countries like the U.S.A.